WERNICKE'S ENCEPHALOPATHY WITH ATYPICAL FINDINGS ON MR IMAGING - Azmat, Zeeshan; Saleem, Munazza; Ahsan, Humera; Mahmood, Kashif (Journal of Ayub Medical College Abbottabad, 2007)
Wernicke's encephalopathy (WE) is a disease usually related to chronic alcoholism. The clinical diagnosis is often difficult to establish. MR imaging is a highly sensitive method for detecting lesions associated with Wernicke's encephalopathy. We report a case of atypical manifestation of hyperintense lesions on magnetic resonance imaging (MRI) in a 60-year-old male patient with Wernicke's encephalopathy. KEY WORDS: Wernicke's; encephalopathy; thiamine; alcohol.